Effects of Nutritional Interventions on Athletic Performance - Toon, A.; Bailey, S.; Roelands, B. (Nutrients, 2023)
The search to comprehend the fundamental physiological factors that contribute to the exceptional endurance performance of elite human athletes is a long-standing endeavor within the field of sports science research [1]. Even today, this search remains a central focus. Currently, a significant portion of research is aimed at unravelling the role of nutritional interventions in athletic performance. As stated in the IOC consensus statement, athletes use dietary supplementation (among others) for supporting their energy metabolism, correcting deficiencies, and achieving either direct or indirect ergogenic effects [2]. There are many systematic reviews [3,4,5,6,7] and consensus statements [2,8,9,10,11] on athletes` dietary supplementation, especially for macronutrients (e.g., glucose, protein, and ketone supplementation, among others) and micronutrients (e.g., nitrate, vitamin, caffeine, and electrolyte supplementation, among others). Therefore this editorial is focused on the emerging, but yet to be further researched, supplementation with substances (i.e., probiotics, prebiotics, and short-chain fatty acids (SCFAs)) that affect the gut microbiome. The gastrointestinal tract (GIT) is inhabited by trillions of not only bacteria, but also viruses, fungi, and archaea [12]. With approximately nine million genes [13], this environment represents the human gut microbiome, which makes up a complex ecological community by which an individual lives in a symbiotic manner all his life [14]. The gut microbiome has versatile functions, such as energy production, regulating the immune system, producing hormones, and communicating with the brain [8,15]. This has ensured that, in the last ten years, a significant interest in understanding the connection between exercise and the gut microbiome has arisen.